Thermotaxis of mammalian sperm. (27th July 2022) - Xiao, Wanglong; Yu, Mengdi; Yuan, Yan; Liu, Xingzhu; Chen, Ying
Abstract: Sperm are guided through the female reproductive tract. A temperature difference of about 2°C exists between the storage site and fertilization site of the mammalian oviduct, leading to the hypothesis that sperm can sense and swim towards the oocyte along a rising temperature gradient, known as thermotaxis. Research over the past two decades has reported that sperm feature a sophisticated thermal detection system to detect and track ambient temperature gradients. More recently, thermotaxis is expected to be added to the microfluidic isolation method based on sperm tactic responses for sperm selection. In this article, mammalian sperm thermotaxis is discussed, explaining the underlying behavioural mechanisms and molecular basis, according to the latest research. Finally, this article explores the possible application of sperm thermotaxis in ART.